Molecular Docking, ADMET Study, Synthesis, Characterization and Preliminary Antiproliferative Activity of Potential Histone Deacetylase Inhibitors with Isoxazole as New Zinc Binding Group - Mohammed Saeed, Ali; Ayad Abed Ali Al-Hamashi (Iraqi Journal of Pharmaceutical Sciences, 2023)
Histone acetylation is a highly interesting epigenetic target for drug therapy. Histone deacetylase enzymes (HDACs) are overexpressed in several diseases, including cancers. Most of the clinically used HDAC inhibitors involve hydroxamate group as a zinc-binding group (ZBG). Hydroxamates have a poor pharmacokinetic properties and high toxicity profile. Therefore, developing non-hydroximate HDAC inhibitors is a promising strategy for potency and selectivity enhancement. In this work, we designed new HDAC inhibitors with isoxazole moiety as ZBG using Ligand Designer from Glide (Schrodinger LLC). The cap group and the linker were optimized through trying various aliphatic and aromatic residues. The potential inhibition over HDAC8 for the optimally designed products was virtually evaluated using licensed Schrodinger modelling software. The results showed that the isoxazole has a potential bidentate interaction with HDAC8 active site zinc ion with acceptable fitness. ADMET/tox study performed to predict the pharmacokinetic properties for the final compounds. The final compounds showed a decent estimated drug-like properties. The intermediates and final compounds were successfully synthesized and purified using column chromatography. The chemical structure for intermediates and final compounds were characterized by IR and NMR spectroscopy.